Pengaruh Intellectual Capital Dan Corporate Social Responsibility Terhadap Nilai Perusahaan Dengan Kepemilikan Manajerial Sebagai Variabel Moderasi - Indriani, Rika; Mansur, Fitrini; Hernando, Riski (Magister Ilmu Akuntansi Universitas Jambi, 2025)
This study aims to determine the effect of intellectual capital and corporate social responsibility on firm value, as well as the role of managerial ownership as a moderating variable. The study was conducted on mining companies listed on the Indonesia Stock Exchange (IDX) during the 2021–2023 period. This study was quantitative and employed a documentary method. The sampling technique used purposive sampling, resulting in a sample size of 17 companies, with a total of 51 companies meeting the criteria. The data used were secondary data from the companies' annual reports and sustainability reports. The data analysis technique used SPSS version 26. The results showed that intellectual capital had a significant positive effect on firm value, while corporate social responsibility had a significant negative effect. Furthermore, managerial ownership moderate the relationship between corporate social responsibility and firm value. These results imply that consistently improving the management of intellectual capital and corporate social responsibility can be an important strategy to increase the value of mining companies. Furthermore, management is advised to consider ownership structure as part of the company's strategic policy.